Sustainability in Construction Engineering - Jurgita Antuchevičienė (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The concept of sustainability has been expanding to all areas of economic activity, including construction. The Special Issue "Sustainability in Construction Engineering" provided a possibility for researchers to disseminate their new ideas and findings related to sustainable decisions in construction engineering as a complex discipline that involves designing, planning, construction and management of infrastructures. The topics raised interest of researchers all over the world and the current Special Issue received a great number of submissions from different institutions, countries and continents. In this Special Issue Reprint, 27 selected and peer-reviewed papers contribute to sustainable construction by offering technological, economic, social and environmental benefits through a variety of methodologies and tools, including fundamental decision-making models and methods as well as advanced multi-criteria decision-making (MCDM) methods and techniques that proved to be very suitable for sustainability assessment. The papers are mainly concentrated in five areas: sustainable architecture; construction/reconstruction technology and sustainable construction materials; construction economics, including investments, supply, contracting and costs calculation; infrastructure planning and assessment; project risk perception, analysis and assessment with emphasis on sustainability. Due to its broad scope, the Special Issue Reprint expects to attract a large interest from the research community.